Human neural stem cells dispersed in artificial ECM form cerebral organoids when grafted in vivo. Issue 2 (10th May 2018) - Basuodan, Reem; Basu, Anna P.; Clowry, Gavin J.
Abstract: Human neural stem cells (hNSC) derived from induced pluripotent stem cells can be differentiated into neurons that could be used for transplantation to repair brain injury. In this study we dispersed such hNSC in a three‐dimensional artificial extracellular matrix (aECM) and compared their differentiation in vitro and following grafting into the sensorimotor cortex (SMC) of postnatal day (P)14 rat pups lesioned by localised injection of endothelin‐1 at P12. After 10–43 days of in vitro differentiation, a few cells remained as PAX6 + neuroprogenitors but many more resembled post‐mitotic neurons expressing doublecortin, β‐tubulin and MAP2. These cells remained dispersed throughout the ECM, but with extended long processes for over 50 μm. In vivo, by 1 month post grafting, cells expressing human specific markers instead organised into cerebral organoids: columns of tightly packed PAX6 co‐expressing progenitor cells arranged around small tubular lumen in rosettes, with a looser network of cells with processes around the outside co‐expressing markers of immature neurons including doublecortin, and CTIP2 characteristic of corticofugal neurons. Host cells also invaded the graft including microglia, astrocytes and endothelial cells forming blood vessels. By 10 weeks post‐grafting, the organoids had disappeared and the aECM had started to break down with fewer transplanted cells remaining. In vitro, cerebral organoids form in rotating incubators that force oxygen and nutrients to the centre of the structures. We have shown that cerebral organoids can form in vivo ; intrinsic factors may direct their organisation including infiltration by host blood vessels.